Endogean and cavernicolous Coleoptera of the Balkans. XXVII. A new species of Mayetia Mulsant et Rey, 1875 (Coleoptera: Staphylinidae: Pselaphinae) from Serbia - Hlaváč, Peter; Janák, Jiří (Zootaxa, 2024)
The new species Mayetia serbica sp. nov. is described from the Radan Mountain in southern Serbia. The morphological details as well as the aedeagus is presented. The catalogue of the genus for the Balkan Peninsula with all relevant references is provided.